A informalidade no mercado de trabalho : um desafio institucional permanente para a economia brasileira - Vargas, Juliano (2015)
The informal economy composes the world of work of all the capitalist societies, in lesser or greater extent. In Brazil, historically it is observed that this phenomenon has always been very broad, mostly motivated by and resulting from socio-economic, legal and political context. Due to national idiosyncrasies, since the advent of the labour market in the country, this situation exists in several panoramas and various hues, hindering a better overall performance of the Brazilian economy and denying opportunities for individual and social development over time. Thus, and through the prism of Social and Labour Economics, the aim of this work is to analyze the main conjunctural and structural factors of informality observed in the national labour market in the interregnum 1980-2012, showing the dimension of this problem and exposing their economic and institutional roots, in order to contribute with new elements to the discussion of informality at the national level. The central hypothesis of this research is that high degree of labour informality in Brazil remains essentially – even if subject to historical specificities – at the level of mentalities of the different agents, meaning that before having a national labour market with a high degree of labour informality has been a highly informal Brazilian society. The institution of “informal work” remains an embedded habit even when a change in the socio-economic order occurs, which precludes much of the population access to formal and decent work (according to ILO definition). It is imperative a greater effectiveness of laws and institutional improvements accompanied by coordination and “political will”, grounded by the growing awareness of civil society with regard to the importance of formal work and the evils of the informal work for its citizens and for the nation as a whole. Beyond to the economic and legal aspects, it is suggested as a possible alternative to reduce the degree of labour informality a more consistent consideration of the cultural, historical and behavioral backgrounds together with the embedded social habits that affect and drive them. These last ones are the axes that guide the process of individual and social development. In this sense, this study (of descriptive and analytical nature) is based on systemic and multidisciplinary theories developed by Karl Paul Polanyi and Amartya Kumar Sen, interpreted as artificers of a dignified life, as well as endorsers of the “re-embeddedness” of the economy in the society and, by analogy, the “desembeddedness” of the informality institutionally rooted in the Brazilian society. This will take place as a consequence of the expansion of the instrumental and substantive freedoms in a sort of “circular and cumulative causation” applied to the issue of informality, with the “highly desirable side effect” of socio-economic development. The main contributions of this research emerged precisely from the theoretical conceptions of these two authors along with a convergent nexus established among the Brazilian economy, its institutional unfolding process and the informality in the national labour market during the studied period.